Análise comparativa: sistemas estruturais convencionais e estruturas de lajes nervuradas - Spohr, Valdi Henrique (2008)
This study has as objective to analyze, comparativily, the costs between the conventional structural systems and the rib slabs structural systems in reinforced concrete. Part of the estimated one that had to the great number of structural systems found in the market of the civil construction the professionals they need to opt to one determined type. But many times the adopted choice is not adjusted to the enterprise because each workmanship has characteristics particular architectural, making it difficult the use of a model standard. The work initially brings basic concepts on the subject and a revision bibliographic approaching the criterion of projects, the characteristics and the particularitities of the adopted systems. After that, one becomes the launching and analysis of the structure for the chosen structural systems, getting the quantitative ones of materials, which they see to form the indices defined for comparison. The total costs of the workmanship gotten by means of compositions of prices had been compared arriving itself it a global value for each adopted kind. For that, a building of offices is adopted as object of analysis of this work. And finally makes a comparative analysis on the basis of the unitary costs of each alternative leading in consideration the materials, necessary hand of workmanship and equipment.